2022
DOI: 10.1080/19490976.2022.2055944
|View full text |Cite
|
Sign up to set email alerts
|

Good microbes, bad genes? The dissemination of antimicrobial resistance in the human microbiome

Abstract: A global rise in antimicrobial resistance among pathogenic bacteria has proved to be a major public health threat, with the rate of multidrug-resistant bacterial infections increasing over time. The gut microbiome has been studied as a reservoir of antibiotic resistance genes (ARGs) that can be transferred to bacterial pathogens via horizontal gene transfer (HGT) of conjugative plasmids and mobile genetic elements (the gut resistome). Advances in metagenomic sequencing have facilitated the identification of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 119 publications
1
35
0
1
Order By: Relevance
“…5b). It is speculated that this may also be related to the transfer of ARGs among these pathogenic bacteria [52] or to the survival mechanism by which some pathogenic bacteria borrow certain protein and RNA components from other bacteria to enhance their own reproductive ability [53].…”
Section: Discussionmentioning
confidence: 99%
“…5b). It is speculated that this may also be related to the transfer of ARGs among these pathogenic bacteria [52] or to the survival mechanism by which some pathogenic bacteria borrow certain protein and RNA components from other bacteria to enhance their own reproductive ability [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, we need to be careful when antimicrobial resistance is taken into consideration. It has been reported that antibiotic usage would assist AMR genes’ horizontal transfer in patients [ 10 ]. However, the mechanisms of antibiotic resistance transmission during microbiome modification remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic usage can disrupt the ability of gut micobiota to inhibit pathogen growth, due to the reduction of native bacterial species, therefore causing antibiotic diarrhea [ 9 ]. Antibiotic usage may also enhance horizontal AMR gene transfer from commensal bacteria to pathogens in gut microbiota, through which antibiotic resistant pathogens that are difficult to treat with common antibiotics are created [ 10 , 11 ]. Probiotics are microorganisms that are beneficial to health when supplemented as part of the human diet [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that antibiotics may play a role in CVDs, but the possible drug resistance caused by long-term use of antibiotics is also of concern, as long-term use of antibiotics may disrupt the dynamic balance of intestinal microorganisms [ 553 ]. Therefore, based on the current findings, we believe that more preclinical and clinical studies are needed to clarify the role of antibiotics in the gut microbiota and CVDs, and individualized use of antibiotics in patients with CVDs should also be considered.…”
Section: Promising Therapy Of Targeting the Gut Microbiota In Cvdsmentioning
confidence: 99%